Enhancing Drug Delivery Precision: Development and Optimization of Nanoparticle-Based Formulations for Targeted Therapy in Preclinical Models - Mehrasa Nikandish; Hanzhi Wang; Xinqi Bao; Mohamad Nikandish (European Scientific Journal, ESJ, 2024)
In recent years, the utilization of nanoparticles has proliferated across a wide spectrum of clinical domains. Nanoparticles have been engineered to surmount the constraints associated with free therapeutics and negotiate biological barriers—systemic, microenvironmental, and cellular—that exhibit heterogeneity across diverse patient cohorts and diseases. Mitigating this patient heterogeneity has also been facilitated through precision therapeutics, where tailored interventions have augmented therapeutic effectiveness. Nonetheless, current nanoparticle development predominantly emphasizes the refinement of delivery platforms with a uniform approach. As lipid-based, polymeric, and inorganic nanoparticles undergo increasingly nuanced engineering, there arises the potential for tailoring them to drug delivery in a more personalized manner, ushering in the era of precision medicine. In this Review, we deliberate on sophisticated nanoparticle designs employed in both generalized and precision applications, offering insights into their potential for enhancing precision therapies. We concentrate on advancements in nanoparticle design that surmount heterogeneous barriers to delivery, positing that intelligent nanoparticle design can enhance efficacy in broad delivery applications while facilitating customized designs for precision applications, thereby ultimately enhancing overall patient outcomes.